Influence Supply Chain Management on the Value of Coal Mining Companies - Prima Yunita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to analyze roles supply chain management on company value as proxied by Price to Book Value (PBV). Variable supply chain which is examined is Inventory Turnover (THIS), Receivable Turnover (RTO), Working Capital Turnover (WCTO), and Total Asset Turnover (THIS). The research was conducted on coal mining sub-sector companies listed on the Indonesia Stock Exchange during the 2019-2023 period and quarterly data. The analysis method uses panel data regression with the help of Eviews version 13 software. The research results show that the resulting equation is overall significant. The coefficient of determination is 0.3058. TATO and WCTO have a positive effect on company value, while ITO and RTO have no effect on company value. The variable that has the most influence on company value is TATO.